Auditıory steady-state response hava ve kemik yollarının karşılaştırılması - Efe, Özge (My University, 2007)
Tüm dünyada uygulanmaya başlayan yeni doğan işitmeyi tarama programının yaygınlaşması ile Auditory steady – state davranımların gelecekte işitme kaybını belirlemede kullanılan test bataryalarının içine gireceği tahmin edilmektedir. ASSR ile hava yoluna ait işitme eşiği elde edebilmek mümkündür(7) Bu çalışmanın amacı , yetişkinlerde hava ve kemik yolu davranım eşikleri ile ASSR hava ve kemik yolu eşikleri arasındaki ilişkinin araştırılmasıdır. Çalışma 44 kişi üzerinde yapılmıştır bunlardan 22’si normal işitmeye sahip diğer 22’si ise hafif derecede sensorinöral işitme kaybı olan kişilerdir. Tüm katılımcıların ASSR hava ve kemik yolu işitme eşikleri 500Hz , 1kHz ,2kHz ,4kHz’lerde belirlenmiştir.Çalışmaya katılanlar 20 ile 50 yaş arasındadır. Hafif derecede sensorinöral işitme kaybı olan katılımcıların ASSR hava ve kemik yolu eşikleri ile davranım hava ve kemik yolu eşikleri arasında çok yüksek korelasyon gözlenmiştir.İşitme kayıplı grubun ASSR hava ile kemik yolları karşılaştırıldığında yüksek korelasyon gözlenmiştir.En düşük korelasyon normal işiten katılımcıların ASSR hava ve kemik yolu eşikleri ile davranım hava ve kemik yolu eşikleri arasında gözlendi.Bu nedenle normal işiten katılımcıların ASSR hava ile kemik yolu eşikleri karşılaştırıldığında yüksek korelasyon gözlendi. 11

Comparison of Auditory Steady-State Response Air Conduction and Bone Conduction threshold Auditory steady- state response is an evoked potential whose discrete frequency components remain constant in amplitude and phase over infinite time period. Multiple auditory steady state responses (ASSR) will likely be incoporated into the diagnostic test battery for estimating hearing thresholds in future. The ASSR for air- conduction stimuli can predict accurate behavioral hearing thresholds(7).The purpose of this study was to examine the correlation between auditory stedy-state response thresholds and behavioral thresholds in adults. A second goal was to compare air and bone conduction ASSR thresholds in patients with normal hearing subjects. The other goal was to compare air and bone conduction ASSR tresholds in patients with flat audiometric configuration . 44 adult participated the study 22 subjects with mild sensory neural hearing loss and 22 subjects with normal hearing. ASSR air- bone conduction thresholds were tested and comparied for frequencies of 500Hz ,1000Hz ,2000Hz , 4000Hz between 22 normal hearing subjects between of age 20-50 and hearing loss subjects between 20-50 years. ASSR and behavioral thresholds were strongly correlated in hearing imparied subjects There were no differences in hearing loss subject’s air bone conduction ASSR thresholds.Slightly poorer correlation was obtained in normal hearing subject’s behavioral and ASSR thresholds.On the other hand there were no differences between normal hearing subjects air bone conduction ASSR thresholds. Key words:Auditory steady- state response threshold, Behavioral threshold ,Bone conduction, Air conduction ,Hearing loss subject
Keywords: İşitme; Odyoloji